Geological actions of water - Pottorf, Andrew J. (My University, 1899)
Introduction: Of all the agents that geologically modify the surface of the earth, water is the most important. It exists in the three following well known forms: (1) as invisible vapor; (2) as water; and (3) as ice. By the heat of the sun vast quantities of water vapor are raised from rivers, lakes and seas, all over the world. This vapor rises into the atmosphere and when it is cooled below its point of saturation, it falls to the earth again in the form of rain, hail or snow. It either percolates thru the soil to feed springs or flows over slopes of land to enter a brook or torrent and at last returns to the sea.
Citation: Pottorf, Andrew J. Geological actions of water. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Destructive Actions; Chemical Changes; Physical Agents; Constructive Actions; Theses; Manuscripts (documents)